Dialektika Agama: Harmoni dalam Jemaat Ahmadiyah Studi Living Qur’ān dan Konstruksi Damai di Kelurahan Gondrong Kenanga Tangerang Banten - Adrika Fithrotul Aini (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2015)
Within vast intolerant attitudes toward Jemaat Ahmadiyah, thecommunity at Gondrong Kenanga, Tangerang, Banten, appears to respectand highly support dissimilarity. Gondrong Kenanga is a place where manyreligious people reside, such as Ahmadiyah, NU, Muhamadiyah and others.They live together without conflict, but in harmony and peaceful condition.This article will discribe a concept of peace belonging to Ahmadiyah atGondrong Kenanga, in which it bases on the Qur’ānic doctrine that relatedto pluralism and harmony.